The influence of maternal diet during lactation on milk fatty acid profile and offspring’s adipose tissue thermogenic capacity - Woods, Rachel (2017)
Over the last two decades, obesity has become a major public health concern. Evidence suggests that obesity can be programmed by nutrition in early life. A way to treat/prevent obesity would be a major breakthrough for public health and brown adipose tissue (BAT) has been identified as a potential target for this, due to its propensity to utilise stored energy to produce heat, a process mediated by the uncoupling protein (UCP) 1 gene. In humans and sheep, UCP1 decreases with age. Diet during lactation and subsequent alterations in milk fatty acid profile have not been studied in relation to effects on offspring BAT function. There is evidence from in vitro and rodent studies to suggest the potential for some fatty acids, such as conjugated linoleic acid (CLA), to increase UCP1 expression. The aim of this thesis is to use sheep as a model to investigate the potential to alter the milk fatty acid profile by supplementing ewes’ diet with canola or sunflower oil, as previous research has found these to be effective in increasing milk CLA. I then investigated the effects on offspring in early life, with a particular focus on their BAT and its UCP1 abundance. The perirenal adipose depot was studied due to it being the largest depot in young sheep, which is known to transition from brown to white adipose tissue in the first month of life. In addition to this, I set out to investigate the CLA concentrations of infant formula milk and how they compare to those reported for human breast milk. From the day of delivery, ewes raising two lambs each were supplemented with 3% canola or sunflower oil or fed a control diet. Milk samples and ewe and lamb weights were taken at 7 and 28 days and offspring were tissue and blood sampled at either 7 or 28 days. The mRNA expression several of genes associated with thermogenesis was measured. Results showed that supplementation of ewe’s diet with canola, and to a lesser extent, sunflower oil, resulted in decreases in milk medium-chain saturated fatty acids (SFAs). Both supplements increased milk monounsaturated fatty acids (MUFAs) by ~50%, and total and cis-9, trans-11 CLA by ~80%. In addition, sunflower supplementation increased omega-6 PUFAs by 25% and the trans-10, cis-12 CLA isomer by 177% at 28 days of lactation compared to controls. Female lambs fed by sunflower oil supplemented ewes showed a 50% increase in adipose tissue weights compared with controls. Male and, to a lesser extent, female lambs fed by canola oil supplemented ewes showed increased UCP1 abundance at 28 days of age compared with controls. There was an increase in mRNA expression of other thermogenic genes in the canola females at 7 but not 28 days, however, not in males, so this unlikely to be the main cause of the increases seen in UCP1. Results from my investigation into infant formula showed that CLA was present in 67% of the infant formula milks tested but at lower concentrations to those reported in human breast milk. In conclusion, it is possible to induce changes in ewes’ milk fatty acid profile with dietary supplementation and I have shown that the fatty acid profile of milk received in early life has the potential to affect adipose tissue development and UCP1 gene expression. If in the prevention of the normal decline in UCP1 were to be maintained into adulthood it could improve long-term health by helping to maintain body weight. Further research is now necessary to establish whether this increase in UCP1 is maintained beyond the sampling time points of my investigation.